Civil Servant Entreprneurship â€œDiklatâ€ Management Model Based on Achievement Motivation Training in the Human Resources Development Board of Central Java - Martuti, Martuti; Soesanto, Soesanto; Hardyanto, Wahyu; Haryono, Haryono (The Journal of Educational Development, 2017)
The main purpose of this study is to find the final model of Civil Servant (PNS) entrepreneurship education and training (DIKLAT) management based on Achievement Motivation Training (PMB) which is suitable to be applied in the Human Resource Development Board of Central Java Province. This research employed a research and development (R & D) method. The ten (10) steps contained in the method were modified into three, namely the preliminary stage, the development stage, and the evaluation stage. The data source was civil servants who were attending the education and training program in the Human Resource Development Board of Central Java Province. Data were drawn from the respondents through interviews, open and closed questionnaires, observations, as well as pre and post test. The data were validated using validity and reliability tests. The effectiveness of the model was assessed using pre and post tests. The result of this research shows that the civil servant entrepreneurship education and training management model based on achievement motivation training is feasible to be applied in Regional Human Resources Development Board of Central Java Province. The effectiveness of the model is proven by the pre and post test results showing that it improves the need for achievement/n-Ach) from 5.27 to 8.10, the need for affiliation/n-Aff from 1.80 to 2.00, and the need for power/n-Pow motive from 4.63 to 5.27; there is an increase of each from medium to high category.